2001
DOI: 10.1017/s003382220003856x
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon Challenges Archaeo-Historical Time Frameworks in the Near East: the Early Bronze Age of Jericho in Relation to Egypt

Abstract: Our stratified radiocarbon dates from EB Jericho (Trench III) on short-lived material are significantly older than conventional archaeo-historical time frameworks. The calibrated 14C date of Stage XV Phase li-lii (Early to Middle EB-I Kenyon) is 100–450 years older. Stage XVI Phase lxi-lxii (Early EB-II Kenyon) is 200–500 years older. Stage XVI Phase lxii-lxiii (destructive end EB-II) is 200–300 years older. Stage XVII Phase lxviii a – lxix a (Early EB-III) is 100–300 years older than conventional archaeo-hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 21 publications
3
20
0
Order By: Relevance
“…That such a scenario implies a much longer span for the EB I period than previously acknowledged would seem unavoidable (Braun 2001), although recent work on the later EBA sequences in the Jordan Valley (Fischer 2000;Bruins and van der Plicht 2001;Segal and Carmi 2004) and the southern coast (Anderson 2006) strongly implies that the dates for later EBA assemblages (EB II-III) may have to be revised upwards as well.…”
Section: Introductionmentioning
confidence: 94%
“…That such a scenario implies a much longer span for the EB I period than previously acknowledged would seem unavoidable (Braun 2001), although recent work on the later EBA sequences in the Jordan Valley (Fischer 2000;Bruins and van der Plicht 2001;Segal and Carmi 2004) and the southern coast (Anderson 2006) strongly implies that the dates for later EBA assemblages (EB II-III) may have to be revised upwards as well.…”
Section: Introductionmentioning
confidence: 94%
“…This work is a part of the study conducted with Ayelet Gilboa, Israel Carmi, and Elisabetta Boaretto to investigate the historicity of the "united monarchy" of David and Solomon as described in the Bible (cf. in this volume: Gilboa 2001 and Sharon;Mazar and Carmi 2001;Bruins and van der Plicht 2001; for a recent book-size exposition see Handy 1997). The chronological dilemma is whether the archaeological horizon (designated hereafter "Ir2a") attributed to this putatively historical period does indeed cover the 10th century BCE, or it is some 50-100 years later into the 9th century (Finkelstein 1996(Finkelstein , 1998.…”
Section: The Problemmentioning
confidence: 99%
“…Many archaeologists studying the Ancient Near East have claimed (or complained) that radiocarbon dates are earlier than archaeo-historical dates for the early historical period: for Egypt (Görsdorf et al 1998;Bonani et al 2001), Sumer (Crawford 1991), Israel-Palestine (Bruins and van der Plicht 2001;Mazar 1992), Italy (Guidi and Whitehouse 1996), and the Aegean (Dickinson 1994), among others. Indeed, in a 2001 issue of Radiocarbon that was devoted to Ancient Near Eastern chronology, the introductory survey paper concluded that the "Collective evidence … clearly indicates … major chronological" disparities between 14 C and archaeo-history for the early historical period (Bruins 2001).…”
Section: Introductionmentioning
confidence: 99%